Principle-oriented versus Information-oriented approach towards Neuroanatomy: A Selective Profile of Neuroanatomy Textbook (Journal of Current and Advance Medical Research, 2025)
Background: Neuroanatomy is an integral part of the undergraduate medical curriculum and it is often considered by students as a difficult subject. It is assumed that students learning may be facilitated if learning and its assessment are structured around generalizable rules or ‘principles’ of the subject rather than trying to memorise plenty of apparently disconnected ‘information’.Objective: Write here the general objective of the study in a single sentenceMethodology: Current edition of two Neuroanatomy textbooks that are commonly recommended for medical undergraduates was analyzed. It was a cross-sectional, observational and descriptive study.Results: Analyses of the textbooks revealed that the mean proportion (±SD) of sentences presenting primarily ‘Principle-oriented text’ is 24.52 (±4.41)% and the mean proportion of sentences (±SD) presenting primarily ‘Information-oriented text’ is 75.48 (±4.41)%. The mean proportion (±SD) of illustrations having ‘Principle-oriented aspect’ is 27.10 (±3.21)% and the mean proportion (±SD) of illustrations having ‘Information-oriented aspect’ is 72.89 (3.21)%.Conclusion: The results of present study provide a baseline data on the principle-oriented aspect of neuroanatomy textbooks which are commonly recommended in Bangladesh. The study also suggest that the issue of principle-oriented approach in the teach-learning and assessment of neuroanatomy is a valid issue to be addressed in the undergraduate curriculum planning and implementation.Journal of Current and Advance Medical Research, July 2024;11(2):79-87